Studi Eksperimental dan Analisis Statistik Multifaktorial terhadap Pengaruh Komposisi Limbah Plastik, Limbah Serabut Kelapa, Fly Ash, dan Gipsum sebagai Bahan Substitusi dalam Pembuatan Papan Semen Ramah Lingkungan - Ardina Kusuma, Yessie; Ridho Akbar (Jurnal Fisika Unand, 2025)
This study develops an environmentally friendly cement board through the utilization of polypropylene (PP) plastic waste, coconut fiber, fly ash, and gypsum. The research aims to analyze the effect of material composition variations on the physico-mechanical characteristics according to SNI 03-2105-2006 standards and to determine the optimal formulation through a multifactorial statistical approach. The research methodology employed a 5×3 factorial design with two main factors: PP to coconut fiber ratio (10:30, 15:25, 20:20, 25:15, 30:10) and fly ash to gypsum ratio (24:36, 30:30, 36:24), resulting in 15 composition variations with three replications each (total 45 samples). Statistical analysis utilized Shapiro-Wilk normality test, Levene's homogeneity test, two-way ANOVA, and Tukey HSD post-hoc test. The results indicate that all formulations met the standard requirements for water content (1.48-4.51%) and density (0.84-0.91 g/cm³). However, the modulus of rupture values (3.67-8.71 kgf/cm²) did not meet the minimum standard for type 8 boards (82 kgf/cm²). Statistical analysis revealed highly significant effects of fly ash-gypsum composition on modulus of rupture (f-value=554.41; p-value<0.001) and component interactions on density (f-value=16.148; p-value<0.001). The optimal formulation was identified at PP:fiber ratio of 20:20 and fly ash:gypsum ratio of 24:36. It is concluded that this material shows potential for non-structural applications such as partitions and interior panels, but requires further optimization through process modifications and additive incorporation to enhance its mechanical performance.